Galois fields elements modified multipliers features and structural complexity - Trishch, Hanna (Lviv Polytechnic Publishing House, 2016)
In this work Binary Galois field GF(2m) elements multipliers structural complexity and its components decreasing has investigated. Elements of fields are represented in the normal basis of type 2. The degree of the field is less then 998.
Keywords: structural complexity; Galois field; matrix multiplier